2022
DOI: 10.55942/pssj.v2i1.140
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence employee’s retention rate in financial technology startups in Indonesia

Abstract: The current human resource management (HR) and brand marketing (Employer Branding) issues are recruiting and retention approaches that 'involve internally and externally encourage a clear vision of what makes a business different and attractive as a business. Sampling is done using probability sampling techniques, namely sampling techniques that provide equal opportunity or opportunity for each member of the population to be selected as a sample. This method is carried out when members of the population are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Research has shown that factors such as employer branding, organizational commitment, and talent management practices significantly influence employee retention [21,22,23]. Additionally, the work environment, engagement levels, and recognition and compensation strategies are vital for retaining employees [24,25]. Employee retention strategies are integral to overall business strategies, emphasizing the importance of careful measures [26,27].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Research has shown that factors such as employer branding, organizational commitment, and talent management practices significantly influence employee retention [21,22,23]. Additionally, the work environment, engagement levels, and recognition and compensation strategies are vital for retaining employees [24,25]. Employee retention strategies are integral to overall business strategies, emphasizing the importance of careful measures [26,27].…”
Section: Review Of Related Literaturementioning
confidence: 99%